Effects of the golfer–ground interaction on clubhead speed in skilled male golfers. Issue 2 (4th March 2019) - Han, Ki Hoon; Como, Christopher; Kim, Jemin; Lee, Sangwoo; Kim, Jaewoong; Kim, Dae Kyoo; Kwon, Young-Hoo
ABSTRACT: The purposes of this study were to characterise the golfer–ground interactions during the swing and to identify meaningful associations between the golfer–ground interaction force/moment parameters and the maximum clubhead speed in 63 highly skilled male golfers (handicap ≤ 3). Golfers performed shots in 3 club conditions (driver, 5-iron and pitching wedge) which were captured by an optical motion capture system and 2 force plates. In addition to the ground reaction forces (GRFs), 3 different golfer–ground interaction moments (GRF moments, pivoting moments and foot contact moments) were computed. The GRF moment about the forward/backward (F/B) axis and the pivoting moment about the vertical axis were identified as the primary moments. Significant ( p < 0.05) correlations of peak force parameters (all components in the lead foot and F/B component in the trail foot) and peak moment parameters (lead-foot GRF moment and trail-foot pivoting moment) to clubhead speed were found. The lead-foot was responsible for generating the GRF moment, while the trail foot contributed to the pivoting moment more. The instant the lead arm becomes parallel to the ground was identified as the point of maximum angular effort, and the loading onto the lead-foot near this point was critical in generating both peak moments.